Using Digital Microfluidics to Dispense, Combine, and Transport Low-Surface-Energy Fluids. (17th February 2018) - Chock, B. P.; Harding, D. R.; Jones, T. B.
Abstract: Surfactant-containing water droplets were produced using a 75-Vrms pondermotive force operating at 10 kHz. Heat from a 30-V direct-current source, applied to a 2 × 0.1-mm region of the fluid, was instrumental in rupturing a low-surface-energy liquid membrane and forming the droplet. The low voltage allows quick and accurate dispensing of droplets without dielectric breakdown. Nanoliter-sized ( 7.6-nL) butanol-styrene droplets were formed using 133 Vrms at 900 Hz. Microliter-sized oil droplets ( 0.6 to 10.5 μL) were formed using high voltage (460 to 672 Vrms at 100 Hz). Oil-water emulsions were formed and moved horizontally, overcoming frictional and surface tension forces. Large oil droplets were also moved to a wider electrode spacing, where the emulsion can take the spherical shape of a target. This was only achieved by transporting the emulsion down an inclined slope (45 deg) using gravity to augment the electric force. All the steps are in place to form targets from oil-water-oil and water-oil-water emulsions; only the dielectrophoretic centering and polymerization processes, which were demonstrated previously, must be added.